Death and the gaze in Rome, Open City. Issue 3 (1st July 2018) - Parigi, Stefania
The article aims to confront the representation of death in Roma città aperta (Rome, Open City) (Rossellini, 1945). Leaving aside the relationship between real death and fictional death, by which is meant the direct link between the film and historical events (already widely analysed by scholars), the essay employs the epic and heroic dimensions in relation to the narration of death; analyses the representation of the foreigner as a bearer of death; focuses, therefore, on the gaze with which Roberto Rossellini observes death, on the spaces and times of the killings; highlights the symbolic and mythological dimension of the film; and, finally, confronts the figure of the scapegoat and the processes of elaboration of memory and mourning.